New South Wales public‐hospital dietitians and how they feel about their workplace: An explorative study using a grounded theory approach. Issue 2 (4th April 2014) - Milosavljevic, Marianna; Noble, Gary; Goluza, Ivana; Keep, Ashleigh; Ponta, Gabriella
Abstract Aim The hospital environment as a workplace has undergone rapid changes over the last 50 years. Despite this, there has been very little research exploring how dietitians working in hospitals perceive their workplace. Moreover, previous studies in this area have focused predominantly on examining the North American experience of dietitians. Only a handful of previous studies have investigated the experiences of Australian dietitians at different stages of their careers. Therefore this study, in part, addresses a gap in the extant literature by examining how New South Wales (NSW) public‐hospital dietitians perceive their workplace and its influence on their ability to function as healthcare professionals. Methods In 2011, 32 in‐depth interviews were conducted with dietitians from 11 NSW public hospitals. Participants were selected from four career stages: new graduates, mid‐career, specialists and managers. Data from the interviews were analysed through a grounded theory approach. Results Data analysis revealed that dietitians sought validation of their work experience from five sources within the workplace. In this paper, these five sources have been depicted as a conceptual model labelled the 'Five Sources of Value'. The five sources identified were: acquisition of knowledge; relationships with others; work culture; role clarity; and personal attributes. This study also found the relative importance of these values changed according to the career stage of the individual dietitian. Conclusions The retention and engagement of staff within a hospital environment is an ongoing issue for dietetic managers. The 'Five Sources of Value' identified through this study and their relative influence at different career stages may assist managers in developing workplace strategies that addresses the major areas of concern for many staff. As a result of the qualitative nature of this exploratory study, the generalisability of the findings are limited. To address this limitation, future research may follow a more quantitative approach.